Proposed Business Strategy for "Mie Ayung" in Order to Sustain in Competitive Market - Andre Budiono, Stevanus; Toha, Mohamad (The Indonesian Journal of Business Administration, 2017)
Abstract. Mie Ayung is a noodle shop that was founded by Hendra Paulus in 2005. Mie Ayung is focusing on serving Bangka authentic chicken noodle that taste delicious and affordable for office workers and new small family. Mie Ayung serve homemade product, it’s specialty such as: chicken noodle, pempek (fried fish cake), and Tahu-Kok (fish meat ball, and tofu meat ball). Although the company surviving more than a decade, Mie Ayung having a hard time in today’s competitive environment where the company is struggling to growing with rapidly changing new trend and reading customer preferences. This past year economy and political condition in Indonesia, especially Jakarta, makes the company replanned for opening new outlets due to bad economic conditions which is resulting in fear of not being able to make enough sales to cover the business. Also, the trend of hybrid Instant noodle that currently blooming in Jakarta, has become a challenge for Mie Ayung, the sales and enthusiasm for traditional noodle shop has been decreasing. To solve these problems, the methodological approach will be used by mixing mixing method of integrating quantitative and qualitative data. In-depth structured interviews will be used to completing qualitative data, while quantitative data will be accumulated from questionnaire; which, using SWOT matrix, TWOS matrix, and the Porter’s three generic strategies, the best strategy for Mie Ayung can be tailored to sustain the business in competitive environment and define different strategy, where the company will emphasize the uniqueness in terms of time, customers, location, and customer relationships in the new business model canvas. In the proposed business plan for Mie Ayung, the company can solve the problem by looking for new approached. Adding more customers by open up and adding its customer segments. As well as give better dining experiences and creates more comfortable space for the customers. The rapid current of trends changing can be challenging, however Mie Ayung can also ride the current and having fun. Mie Ayung can start going online, creating websites and involved in app based food ordering regime; therefore, Mie Ayung can both increasing sales and get exposure to broader audiences.Keywords: Business model canvas, noodles food, Porter’s three generic strategies, restaurant, sustainable competitive advantage, SWOT analysis, TOWS analysis.